1994
DOI: 10.1113/expphysiol.1994.sp003800
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and gestational changes of phosphoethanolamine and taurine in rat brain, striated and smooth muscle

Abstract: SUM NI AR YConcentrations of taurine and phosphoethanolamine in rat smooth (intestinaLl aLnd uterine), skeletal and cardiac muscle, and brain have been determined, using high-performiiance liquid chromatography (HPLC), to examine possible interrelationships in their tissue content. Concentrations were determined in fetal and neonatal samples, as well as in aLdult tissue, to investigate whether phosphoethanolanmine and taurine levels are influenced by developmental st(ate. The effect of gestational state was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…In this sense, taurine immunoreactivity varies in the oocyte and theca cells during follicular development and atresia, in luteal cells during corpora lutea formation and regression, in the oviduct and uterine epithelia comparing pregnant and nonpregnant rats, and in the uterine epithelium during the estrous cycle. Moreover, the decrease in taurine immunoreactivity observed in the oviduct and uterine epithelia during gestation is consistent with the decreased levels in taurine concentration reported in the uterus and in other tissues with pregnancy Turner et al 1994).…”
Section: Discussionsupporting
confidence: 88%
“…In this sense, taurine immunoreactivity varies in the oocyte and theca cells during follicular development and atresia, in luteal cells during corpora lutea formation and regression, in the oviduct and uterine epithelia comparing pregnant and nonpregnant rats, and in the uterine epithelium during the estrous cycle. Moreover, the decrease in taurine immunoreactivity observed in the oviduct and uterine epithelia during gestation is consistent with the decreased levels in taurine concentration reported in the uterus and in other tissues with pregnancy Turner et al 1994).…”
Section: Discussionsupporting
confidence: 88%
“…Phosphorylethanolamine concentration decreases during cerebral development and this observation is consistent in rodents and humans, paralleling the progression of myelination and cellular proliferation (Blüml et al, 1999;Gyulai et al, 1984;Kulak et al, 2010;Tkáč et al, 2003;Turner et al, 1994;Rao et al, 2003;Wijnen et al, 2010a). Like choline, increased PE metabolism during high cellular proliferation was found in several types of brain tumors and to correlate with tumor malignancy (e.g.…”
Section: Neurotransmitter Metabolismmentioning
confidence: 58%
“…It has been demonstrated that the ovary contains the mRNA of a taurine transporter [44] and that the rat oviduct contains up to 10 µmol taurine/g tissue [45]. Taurine is also present in high concentrations in the rat and human uterus, and its concentration decreases with pregnancy [46], [47]. Despite all these data, the roles of taurine in the female reproductive system are largely unknown and there are no previous studies about its localization in these organs.…”
Section: Resultsmentioning
confidence: 99%